Hubungan antara Kebiasaan Membaca Dengan Hasil Belajar Bahasa Indonesia Siswa di SD Inpres 12/79 Macanang - Putri Sahan; Awaluddin Muin; Sitti Jauhar (Universtas Negeri Makassar, 2021)
The problem in this study is the lack of students' reading habits such as rarely visiting the library and when they have free time they do not use it to read so that it can affect their learning outcomes. This study is a quantitative study with a correlational design that aims to determine whether or not there is a relationship between reading habits and Indonesian language learning outcomes of students at SD Inpres 12/79 Macanang. Based on the results of inferential statistical analysis, the tcount value (4.166) is greater than the ttable value (1.66365) at a significant level of 5%, thus HO is rejected and H1 is accepted. Indonesian students at SD Inpres 12/79 Macanang.